P104 Coagulation proteins in liver fibrosis: a role for tissue factor and fibrin/fibrinogen. (6th September 2011) - Dhar, A; Kampscheur, M; Sadiq, F; Levene, A; Ladva, S; Poskitt, B; Goldin, R; Thursz, M
Abstract : Introduction: Recent evidence suggests a role for the coagulation cascade in promoting liver fibrosis, but with the exception of thrombin the expression and role of individual coagulation proteins in the pathogenesis of liver fibrosis is poorly understood. Furthering our understanding of the role of specific coagulation proteins is essential when considering viable targets for anti-fibrotic therapies. Aim: To quantify and qualify the expression of tissue factor (TF) and fibrin/fibrinogen in both murine liver fibrosis and human hepatitis C (HCV) related liver fibrosis. Method: C57BL/6J mice (n=7), aged 8 weeks old, were treated with carbon tetrachloride by intraperitoneal injection for a period of 4 weeks to induce liver fibrosis. Animals were then culled and livers extracted and fixed in formalin. Mice injected with normal saline acted as normal controls. For human tissue, archived liver biopsy specimens (n=11) performed for the clinical staging of chronic HCV infection were used. An indirect immunohistochemical detection technique was employed with digital image analysis to qualify and semi-quantify expression of TF and fibrin/fibrinogen in tissue sections. Results: In murine liver tissue, TF and fibrin/fibrinogen were expressed in hepatic sinusoids, peri-fibrotic areas and fibrotic septa. Digital image analysis demonstrated significant upregulation of TF (p=0.002) and fibrin/fibrinogen (p=0.009) in fibrotic vs normal control liver tissue. In HCV human liver tissue, TF and fibrin/fibrinogen were expressed in hepatic sinusoids and fibrotic areas. Digital image analysis demonstrated a significant correlation between TF expression and both fibrosis grade (r=0.71; p=0.015) and inflammatory score (r=0.79; p=0.004). Fibrin/fibrinogen expression was significantly correlated with inflammatory score (r=0.82; p=0.007), with a borderline correlation with grade of fibrosis (r=0.66; p=0.056). A significant correlation between TF and fibrin/fibrinogen expression was demonstrated (r=0.82; p=0.024). Conclusion: The hepatic expression of TF and fibrin/fibrinogen is upregulated with fibrosis and inflammation. These findings suggest that activation of the coagulation cascade occurs in and may contribute to the generation of hepatic fibrosis. The therapeutic potential of targeted inhibition of specific coagulation proteins need to be evaluated in fibrotic liver disease.